An Insight into the Endophytic Bacterial Community of Tomato after Spray Application of Propiconazole and Bacillus subtilis Strain NBRI-W9 - Udit Yadav; Nasreen Bano; Sumit Bag; Suchi Srivastava; Poonam C. Singh (Microbiology Spectrum, 2022)
ABSTRACT Propiconazole (PCZ) is a commonly sprayed fungicide against fungal pathogens. Being systemic in action, it reaches subcellular layers and impacts the endophytes. Although PCZ is a fungicide, it is hypothesized to exert an inhibitory effect on the bacterial endophytes. Therefore, this study aims to get an insight into the perturbations caused by the systemically acting antifungal agents PCZ and Bacillus subtilis (W9) and the consequences thereof. The current study compared the 16S rRNA microbial diversity, abundance, and functions of the endophytic bacterial community of tomato in response to PCZ, W9, and PCZ+W9 application. The implications of these treatments on the development of bacterial speck disease by Pseudomonas syringae were also studied. The culturable endophyte population fluctuated after (bio)fungicide application and stabilized by 72 h. At 72 h, the endophyte population was ~3.6 × 103 CFUg−1 in control and ~3.6 × 104 in W9, ~3.0 × 102 in PCZ, and ~5.3 × 103 in PCZ+W9 treatment. A bacterial community analysis showed a higher relative abundance of Bacillales, Burkholderiales, Rhizobiales, Pseudomonadales, and Actinomycetales in the W9 treatment compared with that in the PCZ treatment and control. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) analysis showed enhanced metabolic pathways related to secretion, stress, chemotaxis, and mineral nutrition in the W9 treatment. Disease severity was greater in PCZ than that in the W9 treatment. Disease severity on tomato plants showed strong negative correlations with Sphingomonas (r = −0.860) and Janthinobacterium (r = −0.810), indicating that the natural biocontrol communities are agents of plant resistance to diseases. Outcomes show that systemic chemicals are a potential threat to the nontarget endophytes and that plants became susceptible to disease on endophyte decline; this issue could be overcome by the application of microbial inoculums. IMPORTANCE Endophytes are plant inhabitants acting as its extended genome. The present study highlights the importance of maintaining plant endophytes for sustainable disease resistance in plants. The impact of chemical fungicides and biofungicides was shown on tomato endophytes, in addition to their implications on plant susceptibility to bacterial speck disease. The observations point toward the deleterious effects of systemic pesticide application on endophyte niches that disrupt their diversity and functions compromising plant immunity.